Come Out West and Be Our Guest - Levi, Saul Moore, G.H.L.
1909 Seattle held its first world's fair, the Alaska-Yukon-Pacific Exposition (AYPE) in 1909. The fair promoted the region's growth and prosperity that had begun with the 1897 arrival of the first shipment of Yukon gold. The lyrics to "Come Out West And Be Our Guest" invite people from all sections of the country to visit the AYPE. The cover shows Mount Rainier above a compass rose and four vignettes representing different parts of the United States. G.H.L. Moore wrote the lyrics to the song, and Sol Levi (b. 1881) wrote the music. Moore published the piece in Seattle. 1 score (6 p.) + 1 part 10.75 x 14 in.